Informasi Dasar dan Penanganan HIV dan AIDS - Pankratius Husein; Asep Purnama; Raasdiana Rovigis (Jurnal Ledalero, 2015)
Pankratius Husein outlines basic information on the HIV virus and AIDS illness, what medication is available, preventative strategies, and healthy lifestyle. Asep Purnama continues with a personal account of how he became interested in HIV and AIDS since a medical student, and the history of the struggle to correct attitudes among medical staff in Maumere as well as in the general population. This includes the story of the establishment of the Voluntary Testing and Counselling Clinic at the District Hospital in Maumere. Rasdiana Rovigis details the formation and activities of the local support group among HIV carriers. Kata-kata kunci: HIV, AIDS, informasi, penanganan, stigmatisasi, support, group.